Abuse of consumer rights in financial service advertising - Śliwa, Jacek; Sadowska, Izabela (Journal of Finance and Financial Law, 2017)
This publication pertains to disclosure requirements which legislator imposes on creditors and credit intermediaries already at the stage of advertising consumer credits. These obligations, resulting from Consumer Credit Act, are not always respected by financial institution providing this type of service. Such conclusions can be drawn based primarily on last analysis of decisions made by the President of UOKiK, who pointed out numerous irregularities in this scope. In this note disclosure requirements in the field of offering credit services, included in the Consumer Credit Act, will be discussed.